Asuhan Kebidanan Berkelanjutan Ny. ”N’ Di Rumah Sakit Khusus Daerah Ibu Dan Anak Siti Fatimah Makassar Tahun 2023 - Hafsah Hafsah (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Comprehensive midwifery care is a complete examination provided with simple examinations and counseling for pregnancy, childbirth, postpartum, and newborn care. The goal of continuous midwifery care given to Mrs.